Mutagenic drinking water and different levels of emerging micropollutants in Southern Brazil: A new challenge - Paula Hauber Gameiro; Kauê Hohn Assis; Lívia de Oliveira Rozino; Ismael Krüger Pescke; Tatiane Rocha Cardozo; Flávio Andre Pavan; Vera Maria Ferrão Vargas (Environmental Pollution, 2025)

Consistent predictors of microbial community composition across spatial scales in grasslands reveal low context‐dependency - Dajana Radujković; Sara Vicca; Margaretha van Rooyen; Peter Wilfahrt; Leslie Brown; Anke Jentsch; Kurt O. Reinhart; Charlotte Brown; Johan De Gruyter; Gerald Jurasinski; Diana Askarizadeh; Sandor Bartha; et al. (Molecular Ecology, 2023)
Environmental circumstances shaping soil microbial communities have been studied extensively. However, due to disparate study designs, it has been difficult to resolve whether a globally consistent set of predictors exists, or context‐dependency prevails. Here, we used a network of 18 grassland sites (11 of those containing regional plant productivity gradients) to examine (i) if similar abiotic or biotic factors predict both large‐scale (across sites) and regional‐scale (within sites) patterns in bacterial and fungal community composition, and (ii) if microbial community composition differs consistently at two levels of regional plant productivity (low vs. high). Our results revealed that bacteria were associated with particular soil properties (such as base saturation) and both bacteria and fungi were associated with plant community composition across sites and within the majority of sites. Moreover, a discernible microbial community signal emerged, clearly distinguishing high and low‐productivity soils across different grasslands independent of their location in the world. Hence, regional productivity differences may be typified by characteristic soil microbial communities across the grassland biome. These results could encourage future research aiming to predict the general effects of global changes on soil microbial community composition in grasslands and to discriminate fertile from infertile systems using generally applicable microbial indicators.

Cestrum yellow leaf curling virus (CmYLCV) promoter: a new strong constitutive promoter for heterologous gene expression in a wide variety of crops - Livia Stavolone; Maria Kononova; Sandra Pauli; Antonio Ragozzino; Peter de Haan; Steve Milligan; Kay Lawton; Thomas Hohn (Plant Molecular Biology, 2003)

GROWTH LAYER PATTERNS IN TEETH FROM THE FRANCISCANA, PONTOPORIA BLAINVILLEI : DEVELOPING A MODEL FOR PRECISION IN AGE ESTIMATION - Maria Cristina Pinedo; Aleta A. Hohn (Marine Mammal Science, 2000)
A bstract A model for estimating age from teeth of the franciscana, Pontoporia blainvillei , was developed using teeth from 72 specimens taken incidentally in fishing nets in Brazil and Uruguay. The goal of the model was to allow for accurate and precise age estimates for a larger sample of specimens. Growthlayer characteristics were selected on the basis of similarities in growth layers among various species of cetaceans, including those whose growth layers have been calibrated for time, and on length groups in the franciscana, which calves seasonally. Growth‐layer patterns, including relative size and appearance, in both dentine and cementum did not vary by sex but did vary by the orientation of the tooth when it was sectioned. The model developed proved useful in providing guidelines for consistency in age estimation for biological studies of the larger sample of animals. We recommend the development of this type of model for other species to facilitate standardizing age estimation.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)